2014
DOI: 10.1038/nature13489
|View full text |Cite
|
Sign up to set email alerts
|

Host-directed therapy of tuberculosis based on interleukin-1 and type I interferon crosstalk

Abstract: Tuberculosis remains second only to HIV/AIDS as the leading cause of mortality worldwide due to a single infectious agent1. Despite chemotherapy, the global tuberculosis epidemic has intensified because of HIV co-infection, the lack of an effective vaccine and the emergence of multi-drug-resistant bacteria2–5. Alternative host-directed strategies could be exploited to improve treatment efficacy and outcome, contain drug-resistant strains and reduce disease severity and mortality6. The innate inflammatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
801
5
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(859 citation statements)
references
References 32 publications
40
801
5
13
Order By: Relevance
“…IL-1b-dependent host resistance to M. tuberculosis infection was linked to production of eicosanoids through induction of the enzyme cyclooxygenase-2 (gene known as Ptgs2) (13). We confirmed that blockade or absence of IL-1R signaling in murine and human macrophages is associated with reduced PTGS2 induction (Fig.…”
Section: Resultssupporting
confidence: 71%
“…IL-1b-dependent host resistance to M. tuberculosis infection was linked to production of eicosanoids through induction of the enzyme cyclooxygenase-2 (gene known as Ptgs2) (13). We confirmed that blockade or absence of IL-1R signaling in murine and human macrophages is associated with reduced PTGS2 induction (Fig.…”
Section: Resultssupporting
confidence: 71%
“…It improves survival of Mtb-infected mice. 104 The eicosanoid pathway thus represents a complex target of TB HDT as the effect is likely dependent on infection stage, as PGE2 has protective effects early during infection but impairs anti-TB immunity during later stages. 105 …”
Section: Eicosanoid Modulatorsmentioning
confidence: 99%
“…Because IL-10 has been known to exacerbate murine mycobacterial infections under some circumstances (84), IL-10 induction by type I IFNs could be one mechanism by which type I IFNs impair resistance to mycobacterial infection (85)(86)(87). Interestingly, a recent study suggests that M. tuberculosis-induced type I IFN production can be regulated by IL-1b through PGE 2 (88). PGE 2 administration suppresses type I IFN production and increases survival in treated mice, suggesting a cross-regulation between the IL-1b and type I IFN pathways and that antagonism of type I IFN production via PGE 2 could be used as a potential therapy for active TB.…”
Section: Mycobacteriamentioning
confidence: 99%